A checklist of familial and suprafamilial names for extant vascular plants - Reveal, James L. (Phytotaxa, 2013)
Family and suprafamilial names are reconsidered following changes made at the 2005 Botanical Congress held in Vienna, Austria. The purpose of this document is to update the information provided by Hoogland and Reveal that same year. The formal establishment of 4 Aug 1789 as the starting date for vascular plant suprageneric names negated a series of names established mainly at the ranks of class and family from 1763 until 1788. The decision not to require parenthetical authorships above the rank of genus resolved a long-standing ambiguous feature of the International Codeof Botanical Nomenclature. The third change resulted in the recognition of a series of names at the ranks of order, suborder, family and subfamily traditionally considered to be at misplaced ranks, and as a result altered hundreds of authorships and places of publication for long-recognized names. It also rendered invalid numerous names below the rank of family that have never been considered to be in nomenclatural difficulty. The full extent of the changes below the rank of family is unknown. This checklist attempts to resolve the issue for the majority of family and suprafamilial names, but to accomplish the task of knowing all of the changes will require another detailed review of a subset of the systematic literature published mainly from 1820 to approximately 1895. The checklist is arranged in five parts: (a) the main listing with all names arranged alphabetically, (b) a listing of names by rank, (c) a listing of names by date of publication, (d) a listing of names by author and date of publications, and (e) family names in current use.